The prediction of local goat live body weight in Tamimi at Al-Jabal Al- Akhdar region (Libya) - Amaizik, Salem A. (Al-Mukhtar Journal of Sciences, 2014)
This study was conducted in the east of Al-Jabal Al-Akhdar (Tamimi region), Libya to predict live body weight of 10 adult local goat females (weight ranged 35-55 kg, age ranged 2-4 years) and 10 adult local goat males (weight ranged 55-85 kg, age ranged 3-5 years) using linear equations. Measurements of various external body regions used in the prediction were body length, and the circumference of abdomen, thoracic and foreleg cannon, and the height of abdomen, thoracic and shoulder. These regions were used singly or together. The highly correlation (R2) values with body weight of all animals were thoracic circumference (0.97) and shoulder height (0.92). While, the lowest values were thoracic height (0.63) and abdomen height (0.65). The correlation values were high with male than female weights. For males, the highest values were obtained from thoracic circumference (0.98) and abdomen circumference (0.96). For females, the highest values were obtained from shoulder height (0.80) and abdomen circumference (0.80). The equation for all animals to predict live body weight was: live weight (kg) = [thoracic circumference, (cm) X 1.78]– 98.39. The inclusion of two regions measurements improved the prediction, and the equation was: live weight (kg) = [shoulder height, (cm) X 0.44] + [thoracic circumference, (cm) X 1.39] – 104.25. For males, the equation was: male live weight (kg) = [thoracic circumference, (cm) X 0.98] + [abdomen circumference, (cm) X 0.82] – 108.4. For females, the equation was: female live weight (kg) = [shoulder height, (cm) X 0.76] + [abdomen circumference, (cm) X 0.70] – 88.2. It could be concluded that live body weight of fattening local Libyan goats could be predict with high degree of precise with using some external body region measurements